Atrial fibrillation and its relation to alcohol consumption in the general population: The seventh survey of the Tromsø Study. - Anwar Ul Haq, Muhammad (UiT Norges arktiske universitet, 2024)
Background: Atrial fibrillation (AF), the most prevalent cardiac arrhythmia, characterized by disruption of the electrical activity in atria, leading to the cardiac rhythmic disorder. Alcohol consumption has dose-dependent relationship with cardiovascular diseases and considered as a contributing factor for incidence of AF. Epidemiological studies have consistently shown a dose-dependent relationship either linear or J-shaped between alcohol consumption and the risk of AF incidence. Sex differences in the relationship between alcohol consumption and AF have been documented in various studies. This study primarily aims to investigate the sex-specific associations between alcohol consumption and the incidence of AF. Aim: The objective of this study is to explore the relationship between alcohol consumption and incidence of AF among men and women in the 7th survey of the Tromsø study. Material and Methods: This population-based longitudinal cohort study using data from Tromsø7 (2015-2016). All inhabitants aged 40 years and older in the Tromsø municipality (n = 32,591) were invited to participate. A total of 21,083 participants aged between 40 and 99 attended the survey, resulting in a participation rate of 64.7%. Complete case analyses were performed, and the final cohort consisted of 17243 participants among these 8,280 were men and 8,963 were women. Physical examination was conducted within municipality and alcohol variables and potential confounders were assessed by using a comprehensive questionnaire (Q1). Statistical analyses were performed using IBM SPSS. Descriptive statistics were used to present continuous variable as means (SD) and categorical variables as proportions. To examine the association between alcohol consumption (including drinking patterns and alcohol) and incidence of AF, Cox proportional hazards regression analysis was utilized to calculate hazard ratios (HRs) with 95% CIs. All analyses were conducted with a focus on sex differences. Results: The sex-stratified Cox regression analysis ...